Refractory Bergmann type A bile leak: the need to strike a balance - Mutignani, Massimiliano; Forti, Edoardo; Larghi, Alberto; Dokas, Stefanos; Pugliese, Francesco; Cintolo, Marcello; Bonato, Giulia; Tringali, Alberto; Dioscoridi, Lorenzo (Endoscopy International Open, 2019)
Background and study aims Endoscopic therapy for postoperative Bergmann type A bile leaks is based on biliary sphincterotomy ± stent insertion. However, recurrent or refractory bile leaks can occur. Patients and methods This was retrospective study including all consecutive patients who were referred to our center with a Bergmann type A bile leak refractory to previous conventional endoscopic treatments. Results Seventeen patients with post-cholecystectomy-refractory Bergmann type A bile leak were included. All had received prior endoscopic biliary sphincterotomy with biliary stent or nasobiliary catheter placement and all had a percutaneous or surgical abdominal drainage. Repeat endoscopic retrograde cholangiopancreatography (ERCP) confirmed a Bergmann type A bile leak and in all patients we observed that the abdominal drainage was placed adjacent to the origin of the fistula. Our treatment consisted of pulling the drain away from the fistulous site, with extension of the previous sphincterotomy when needed. The treatment was successful in all cases. Mild complications occurred in three patients. Conclusions Our retrospective study shows that refractory Bergmann type A bile leak may be a consequence of an unfavorable position of the abdominal drainage tube, which can be corrected by pulling the drain away from the origin of the fistula. This establishes a favorable pressure gradient that leads the bile flowing from the bile duct into the duodenum.